Differential responses of soil bacterial communities to long-term N and P inputs in a semi-arid steppe - Ling, Ning; Chen, Dima; Guo, Hui; Wei, Jiaxin; Bai, Yongfei; Shen, Qirong; Hu, Shuijin (Geoderma, 2017)
Both nitrogen (N) and phosphorus (P) may limit plant production in steppes and affect plant community structure. However, few studies have explored in detail the differences and similarities in the responses of belowground microbial communities to long-term N and P inputs. Using a high-throughput Illumina Miseq sequencing platform, we characterized the bacterial communities in a semi-arid steppe subjected to long-term N or P additions. Our results showed that both the Chao richness and Shannon's diversity were negatively correlated to N input rate, while only Chao richness was significantly and negatively correlated to P input rate. Also, both N and P additions altered the bacterial community structure. The bacterial community between plots of the same N or P input rate was much more dissimilar with the higher input level, indicating more severe niche differentiation in pots with higher N or P input. N Inputs significantly increased the relative abundance of the predicted copiotrophic groups (Proteobacteria and Firmicutes) but reduced the predicted oligotrophic groups (Acidobacteria, Nitrospirae, Chloroflexi), with the order Rhizobiales being most affected. P additions significantly affected only two phyla (Armatimonadetes and Chlorobi), which were positively correlated with P source. Results from the structural equation modelling (SEM) showed that N additions affected the bacterial community primarily by changing the pH, while P additions did so mainly by improving P availability. Our results suggest that the below-ground bacterial communities are more sensitive to N inputs, but P inputs can also play an important role in bacterial niche differentiation. These findings improve our understanding of bacterial responses to N and P inputs, and their impacts on bacterial-mediated processes, especially in the context of increasing anthropogenic nutrient inputs. •Responses of soil bacterial communities to long-term N and P inputs in a steppe were compared.•Both N and P inputs altered the bacterial community but in a different manner.•Severer bacterial community dissimilarity was found by higher N and P inputs.•N inputs affect bacterial community primarily by changing the pH.•P inputs affect the community primarily via mediating P availability.